Body Weight Changes During Pandemic-Related Shelter-in-Place in a Longitudinal Cohort Study - Lin, Anthony L; Vittinghoff, Eric; Olgin, Jeffrey E; Pletcher, Mark J; Marcus, Gregory M (JAMA Network Open, 2021)
This cohort study investigates whether the shelter-in-place orders in the US during the early weeks of the COVID-19 pandemic were associated with changes in body weight among adults.